Analysis Of Agroforestry Development Strategy For Economic Improvement And Environmental Quality (A Case Study Of Idfos Indonesia Agroforestry Program) - Falasifah, Nihlatul; Firdausi, Rizal Zubad; Sunariyo, Sunariyo; Nabihah, Evita Zuhnun; Choirunnisa, Illa; Rosyda, Fatya Nur; Syaroh, Nisaatu Umay (IDFoS Indonesia, 2021)
This research aimed to determine the effectiveness of agroforestry management development strategies in an effort to improve the economy and environmental quality in the forest area of Bandungrejo Village, Ngasem Sub District, Bojonegoro Regency through a SWOT analysis. This research used qualitative research using purposive sampling technique, it was the researchers determined the informants based on certain characteristics by considering the knowledge of the informants related to the phenomena studied. The location of this research was in the Perhutani KPS plots 41, 53, and 54 in Bandungrejo Village, Ngasem Sub District, Bojonegoro Regency with LMDH Rimba Tani as the target group for one month. The collected data was then analyzed using the SWOT method. The results showed that an effective development strategy used to improve the economy and environmental quality in forest areas was in quadrant II, it was supporting strategies to avoid the impact of threats (ST). ownership of each member, making compost and vegetable pesticides, developing agroforestry patterns with the application of appropriate technology to increase land productivity and production of economic benefits.